2021
DOI: 10.3389/fncel.2021.627682
|View full text |Cite
|
Sign up to set email alerts
|

Glial Cell-Based Vascular Mechanisms and Transplantation Therapies in Brain Vessel and Neurodegenerative Diseases

Abstract: Neurodevelopmental and neurodegenerative diseases (NDDs) with severe neurological/psychiatric symptoms, such as cerebrovascular pathology in AD, CAA, and chronic stroke, have brought greater attention with their incidence and prevalence having markedly increased over the past few years. Causes of the significant neuropathologies, especially those observed in neurological diseases in the CNS, are commonly believed to involve multiple factors such as an age, a total environment, genetics, and an immunity contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 125 publications
0
7
0
Order By: Relevance
“…Aβ clearance can be mediated by microglia. In addition, Aβ can also be cleared through vascular access [ 57 ], the glymphatic system [ 58 ], and IPAD [ 59 ]. IPAD failure can lead to cerebral amyloid angiopathy (CAA), where Aβ mainly accumulates in capillaries and arterial smooth muscle cells BM [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aβ clearance can be mediated by microglia. In addition, Aβ can also be cleared through vascular access [ 57 ], the glymphatic system [ 58 ], and IPAD [ 59 ]. IPAD failure can lead to cerebral amyloid angiopathy (CAA), where Aβ mainly accumulates in capillaries and arterial smooth muscle cells BM [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…26 Astrocytic and neuronal vasoactive substances may also activate Ca 2+ signalling in small arteries. 27 Astrocytes mediate the neurovascular units and capillary components at the capillary level, inducing an increase in intracellular Ca 2+ in astrocytes through a purinergic receptor P2X release mechanism. 27 It has been shown that nimodipine significantly reduced symptoms caused by secondary ischaemia after SAH.…”
Section: Discussionmentioning
confidence: 99%
“…27 Astrocytes mediate the neurovascular units and capillary components at the capillary level, inducing an increase in intracellular Ca 2+ in astrocytes through a purinergic receptor P2X release mechanism. 27 It has been shown that nimodipine significantly reduced symptoms caused by secondary ischaemia after SAH. 28 Currently, nimodipine is considered as the first choice for the prevention of CVS after SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes serve as power reservoirs and help neurons resist ischemic injury by storing glycogen (Gurer et al, 2009) and transferring mitochondria (Hayakawa et al, 2016). Astrocytes can also secrete neurotrophic factors (Pekny et al, 2016;Zhao et al, 2021) to alleviate neuronal death. However, hypoxic astrocytes become highly swollen and cannot clear glutamate (Menyhart et al, 2021), thus aggravate neuronal excitotoxicity.…”
Section: General Responses Of Neurovascular Units To Ischemic Injurymentioning
confidence: 99%